Deciphering the Late Paleozoic–Cenozoic Tectonic History of the Inner Central Andes Forearc: An Update From the Salar de Punta Negra Basin of Northern Chile - Martínez, Fernando; Parra, Mauricio; Gonzalez, Rodrigo; López, Cristopher; Ana, Patiño; Muñoz, Belén; Robledo, Francisca; Sobel, Edward R.; Glodny, Johannes (Frontiers in Earth Science, 2022)
We integrated new and existing geological, geochronological, thermochronological, and two-dimensional (2D) seismic data from the Salar de Punta Negra Basin to define the Late Paleozoic–Cenozoic tectonic evolution of the inner Andean forearc of northern Chile more precisely. Our results indicate that this region experienced early Late Paleozoic–Mesozoic (Triassic and Jurassic) crustal extension, creating several basement half-graben structures bounded by east- and west-dipping master faults. These extensional basins were filled by Upper Permian to Jurassic volcanic and sedimentary (continental and marine) syn-rift deposits. The genesis of these structures is related to the early breakup of the western Gondwana continent and the development of the large Tarapacá Basin in northern Chile and southern Perú. Subsequently, Late Cretaceous to Paleocene contraction occurred, which led to the tectonic inversion of the pre-existing rift system and the uplift of the Paleozoic–Mesozoic syn-rift deposits. Seismic data show that Upper Cretaceous and Paleocene synorogenic deposits accumulated along and over inversion anticlines, recording the initial contraction and marking the change from an extensional to a contractional tectonic setting. During the final episodes of basin inversion, crustal shortening was accommodated by the Eocene to recent basement reverse faulting accompanied by the rapid exhumation of basement pre-rift blocks, which served as the principal sources for the sediments that filled the pre-Andean basins during the Late Cenozoic. Finally, the exhumed basement pre-rift blocks and the reverse faults compartmentalized the contractional intermontane basins, which constitute the main low topographic relief of the inner forearc of northern Chile.